Potassium Release Kinetics from Dioctahedral and Trioctahedral Minerals under Alkaline Conditions (Global Journal of Science Frontier Research, 2018)
The agricultural significance of Potassium (K) has been comprehensively documented owing to its role in plant development and growth. The reserves of K in soil are not available to plant roots for uptake as 98% of the total soil K is mineral bound. The K bearing 2:1 type clay minerals can serve as an enormous and renewable pool of K supply in soil. The K releasing capacity of these minerals is governed by different agents like ionic strength, temperature and pH. Therefore, the release K from dioctahedral (Muscovite) and trioctahedral (Biotite) pure minerals were investigated at 25±1°C in batch reactors over the pH range of 8 to 12. The experiments performed until the steady state was achieved. At the start of each experiment, the high output solutions concentrations of Fe, Si, K and Al were recorded, after that a gradual reduction was observed leading to the establishment of steady state conditions. The release of Kwas more from the dissolution of biotite thanmuscovite dissolution.
Keywords: mica; potassium; biotite; muscovite; alkaline pH; dissolution